A RECENT APPROACH TO CONTINUOUS TIME OPEN LOOP STACKELBERG DYNAMIC GAME WITH MIN-MAX COOPERATIVE AND NONCOOPERATIVE FOLLOWERS - Osman, M.S.; El-Kholy, N.A.; Soliman, E.I. (European Scientific Journal, ESJ, 2015)
Stackelberg games play an extremely important role in such fields as economics, management, politics and behavioral sciences. There exists extensive literature about static optimization problems. However, the studies on dynamic optimization problems are relatively scarce in spite of the importance in explaining and predicting some phenomena rationally. In this paper, new approach of continuous time open loop stackelberg differential game introduced with a min-max game (secure concept) between multiple followers playing dependently (the pareto followers) and others independently (the nash followers), the problem formulation is presented with an example for the solution of the game.